Metabolic Dysfunction-Associated Steatotic Liver Disease MASLD: Jordan’s Perspective Based on Knowledge and Attitude Determinants - Alqudah O; Alshahwan HF; Alsamhouri JF; Yamin S; Kaffaf A; Alassaf M; Alwarawrah Z (Dove Medical Press, 2024)
Omar Alqudah,1 Hamzeh Feras Alshahwan,2,* Jehad Feras Alsamhouri,2,* Saif Yamin,2,* Ahmad Kaffaf,2,* Mohannad Alassaf,2,* Zaid Alwarawrah3 1Department of Medicine, Division of Hepatology and Gastroenterology, Jordan University Hospital and School of Medicine, The University of Jordan, Amman, Jordan; 2School of Medicine, The University of Jordan, Amman, Jordan; 3School of Medicine, University of Mu'tah, Al-Karak, Jordan*These authors contributed equally to this workCorrespondence: Hamzeh Feras Alshahwan, Email alshahwanhamzeh@gmail.comPurpose: The most prevalent chronic liver disease in both developed and developing nations is Metabolic dysfunction-associated Steatotic Liver Disease (MASLD). The condition increases the risk of comorbidities and liver-related morbidity and mortality. The public's awareness and medical personnel's understanding are essential in creating countermeasures to stop the disease's spread; a positive attitude is essential for early screening. This study aimed to explore the knowledge and attitudes of Jordanians living in Amman toward MASLD to determine the public's awareness and medical personnel's understanding of the disease.Materials and Methods: A cross-sectional study was conducted using an online self-administered questionnaire that included 5 items for knowledge and 8 for attitude. Demographic questions were also included to further examine how demographic factors affected knowledge and attitude.Results: Among 906 responders, (63.4%) were females, and (36.6%) were males. The majority age group was 18- 30 (56.2%). Only 49.5% had previous knowledge of MASLD, (44.6%) believed they were at risk of developing it. There is a statistical significance between age, gender, educational level, and having a good knowledge of MASLD and a positive attitude towards it (p< 0.05).Conclusion: Generally, Jordan's population has a fair knowledge of MASLD and a positive attitude towards it. Warranting more research into the reasons behind it, and more awareness campaigns.Keywords: nonalcoholic fatty liver disease, NAFLD, MASLD, hepatic steatosis, liver health, patient education, public health awareness, medical literacy, Metabolic Dysfunction-Associated Steatotic Liver Disease